2015
DOI: 10.1016/j.ajpath.2014.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Myeloid A Disintegrin and Metalloproteinase Domain 10 Deficiency Modulates Atherosclerotic Plaque Composition by Shifting the Balance from Inflammation toward Fibrosis

Abstract: A disintegrin and metalloproteinase domain 10 (ADAM10) is a metalloprotease involved in cleavage of various cell surface molecules, such as adhesion molecules, chemokines, and growth factor receptors. Although we have previously shown an association of ADAM10 expression with atherosclerotic plaque progression, a causal role of ADAM10 in atherosclerosis has not been investigated. Bone marrow from conditional knockout mice lacking Adam10 in the myeloid lineage or from littermate controls was transplanted into le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(23 citation statements)
references
References 32 publications
2
21
0
Order By: Relevance
“…For instance, the genetic deletion of Mas receptor in C57BL/6 mice resulted in an increased inflammatory response to LPS injection, suggesting a potent anti-inflammatory role of this receptor in acute systemic inflammatory disorders [18]. macrophages) [21][22][23], neutrophils still represent a major source of these toxic compounds within mouse plaques [14], where their activity might degrade the protective collagen in the fibrous cap and increase the risk of plaque rupture. Confirming these results, a recent study using male Sprague-Dawley rats, Balb/c and C57Bl6/J mice with acute lung injury showed that antagonism of the Mas receptor with A779 was able to restore neutrophil infiltration within the lungs [20].…”
Section: Discussionmentioning
confidence: 99%
“…For instance, the genetic deletion of Mas receptor in C57BL/6 mice resulted in an increased inflammatory response to LPS injection, suggesting a potent anti-inflammatory role of this receptor in acute systemic inflammatory disorders [18]. macrophages) [21][22][23], neutrophils still represent a major source of these toxic compounds within mouse plaques [14], where their activity might degrade the protective collagen in the fibrous cap and increase the risk of plaque rupture. Confirming these results, a recent study using male Sprague-Dawley rats, Balb/c and C57Bl6/J mice with acute lung injury showed that antagonism of the Mas receptor with A779 was able to restore neutrophil infiltration within the lungs [20].…”
Section: Discussionmentioning
confidence: 99%
“…Assessment of atherosclerosis lesions was performed as described previously (van der Vorst et al, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…ADAM10 has been found to cleave various cell surface molecules, including adhesion molecules, chemokines, and growth factor receptors. ADAM10-deficient macrophages showed reduced migration and extracellular matrix degradation as well as altered IL-10, IL-12, NO, and TNF signaling in mice (van der Vorst et al, 2015). CTSS is a lysosomal cysteine protease that has been implicated as essential in macrophage migration and development by cleavage of Rip1 kinase in mice (Verollet et al, 2011;McComb et al, 2014).…”
Section: Gene Ontology Analysis Shows Role In Primitive Myeloid Activmentioning
confidence: 99%